Targeting γ-secretase in breast cancer - Han, Jianxun (Dove Medical Press, 2012)
γ-secretase complexes are multisubunit protease complexes that perform the intramembrane cleavage of more than 60 type-I transmembrane proteins, including Notch receptors. Since dysregulated Notch signaling has been implicated in the tumorigenesis and progression of breast cancer, small molecule γ-secretase inhibitors (GSIs) are being tested for their therapeutic potential in breast cancer treatment in several clinical trials. Here, the structure of γ-secretase complex and the development of GSIs are briefly reviewed, the roles of Notch and several other γ-secretase substrates in breast cancer are discussed, and the difference between γ-secretase inhibition and Notch inhibition, as well as the side effects associated with GSIs, are described. A better understanding of molecular mechanisms that affect the responsiveness of breast cancer to GSI might help to develop strategies to enhance the antitumor activity and, at the same time, alleviate the side effects of GSI.